2014
DOI: 10.24156/jikk.2014.7.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dukungan Sosial Dan Strategi Nafkah Terhadap Kesejahteraan Subjektif Keluarga Usia Pensiun

Abstract: AbstrakUsia pensiun seringkali identik dengan masa-masa penurunan kesejahteraan baik ekonomi, fisik, psikologis, dan sosial. Lingkungan yang mendukung dan alternatif sumber pendapatan yang tersedia akan menentukan kebahagiaan memasuki masa pensiun. Penelitian ini bertujuan untuk menganalisis pengaruh dukungan sosial dan strategi nafkah terhadap kesejahteraan subjektif keluarga usia pensiun. Desain yang digunakan dalam penelitian adalah cross sectional. Penelitian ini melibatkan 154 keluarga dengan suami dan at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…In order to achieve the goal of syara 'in order to realize the benefits, he outlined the sources of welfare, namely: the maintenance of religion, soul, mind, descent and wealth (Huda, 2015).The results of the research that support this research, according to Raharjo, Puspitawati, & Krisnatuti (2015) found that the better financial management is carried out, the higher the family welfare. Research from Rizkillah, Sunarti, & Herawati (2015) found that the dimensions of marital satisfaction, aspects with the highest achievement were the economy and the lowest were love and intimate relationships.The research is in line with the research ofSulastri & Hartoyo (2014) found that subjective well-being is significantly influenced by family income, social support, and livelihood strategies. Family income has a significant positive effect on subjective wellbeing.…”
supporting
confidence: 89%
“…In order to achieve the goal of syara 'in order to realize the benefits, he outlined the sources of welfare, namely: the maintenance of religion, soul, mind, descent and wealth (Huda, 2015).The results of the research that support this research, according to Raharjo, Puspitawati, & Krisnatuti (2015) found that the better financial management is carried out, the higher the family welfare. Research from Rizkillah, Sunarti, & Herawati (2015) found that the dimensions of marital satisfaction, aspects with the highest achievement were the economy and the lowest were love and intimate relationships.The research is in line with the research ofSulastri & Hartoyo (2014) found that subjective well-being is significantly influenced by family income, social support, and livelihood strategies. Family income has a significant positive effect on subjective wellbeing.…”
supporting
confidence: 89%
“…Perasaan optimis tersebut merupakan bentuk afek positif dari aspek kesejahteraan subjektif (Nuzulia & Nursanti, 2012). Dengan demikian, individu yang menerima dukungan penghargaan dari individu lain cenderung rendah afek negatifnya dan hal ini akan cenderung meningkatkan kesejahteraan subjektif individu tersebut (Sulastri & Hartoyo, 2014).…”
Section: Instrumenunclassified